Piano sonata no. 22 in F major, op. 54, edited by Moscheles - Beethoven, Ludwig van, 1770-1827 (composer):::Creator::::::::::::; Moscheles, Ignaz, 1794-1870 (editor):::Contributor:::::::::::: (E. Gérard; Paris; France, 2024)
Piano sonata no. 22 in F major, op. 54, published by Gérard as for section 3 of the Édition classique des oeuvres spéciales pour piano a deux mains, with pedal markings, fingerings, and Moscheles's metronome markings.